Assessing the Role of Culture in Female entrepreneurship in Contemporary Sub-Saharan society:Insights from The Nabadam District of Ghana - Anambane, G.; Adom, K. (Journal of Developmental Entrepreneurship, 2018)
This study explores the role of cultural practices on female entrepreneurship with some insights from the Nabdam district of Ghana. The views of twenty (20) female entrepreneurs were gathered through face-to-face in-depth interviews, which were analyzed according to identified themes. The key finding of the study is that, because of cultural influences and norms, entrepreneurship is perceived to be a field for uneducated women as highly educated women seek formal employment than self-employment. Also, the value and respect for traditions was found to be a limiting factor to the growth and expansion of female-owned enterprises. Therefore, this study concludes that the general poor performance of female entrepreneurs in the study area can be attributed to long-held traditional beliefs and practices rather than managerial inability on the part of women. The stereotype threat theory is used to explain the state of female entrepreneurship in the study area. Therefore, there is a call on policy makers to formulate policies that could eliminate the negative impact of culture on female-owned businesses.
Keywords: Culture; Female entrepreneurship; Sub-Saharan Africa; Ghana; Rural